2007
DOI: 10.1086/513875
|View full text |Cite
|
Sign up to set email alerts
|

Strain Prevalence, Rather than Innate Virulence Potential, Is the Major Factor Responsible for an Increase in Serious Group A Streptococcus Infections

Abstract: These data suggest that the emergence of GAS strains with increased virulence is not the main factor responsible for the surge in GAS-related infections. The prevalence of particular emm types, RAPD profiles, or superantigen genes in invasive disease may simply indicate widespread transmission of these strains in the population, rather than a particular ability to cause disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
43
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 41 publications
9
43
2
1
Order By: Relevance
“…Together, these observations suggest that, rather than being isolated at constant rates, individual emm types and subtypes display features of epidemic behavior, constantly expanding and subsiding as a result of host immune selective pressure. The isolation frequency for emm types from different GAS diseases generally parallels their rate of asymptomatic carriage in the same population (57). However, there are significant associations of some emm types with particular disease manifestations ( Table 1).…”
Section: Epidemiology Of Gas Infectionsmentioning
confidence: 93%
“…Together, these observations suggest that, rather than being isolated at constant rates, individual emm types and subtypes display features of epidemic behavior, constantly expanding and subsiding as a result of host immune selective pressure. The isolation frequency for emm types from different GAS diseases generally parallels their rate of asymptomatic carriage in the same population (57). However, there are significant associations of some emm types with particular disease manifestations ( Table 1).…”
Section: Epidemiology Of Gas Infectionsmentioning
confidence: 93%
“…However, variation among serotypes explains only part of the variation in infection type [11,12,17], the residual typically being ascribed to variation among host individuals. Here we explore another factor that may contribute: bacterial epigenetic regulation of virulence.…”
Section: An Epigenetic Mechanism For Virulence Bistabilitymentioning
confidence: 99%
“…However, some GAS serotypes are biased towards a given infection type, which shows that the bacterium also plays a role in determining the type of infection. For example, the serotypes M1 and M12 are both able to cause all three types of infection, but M1 is overrepresented in symptomatic infections, whereas M12 is more prone to be asymptomatic [11,12]. Similarly, a large study performed at the Centers for Disease Control and Prevention (CDC) found that the M1 serotype was significantly associated with invasive infection, and M12 with noninvasive infection [13].…”
mentioning
confidence: 99%
“…Although many GAS serotypes are capable of causing severe diseases, a few were more frequently isolated from patients with severe cases, e.g., M1, M3, M18, and M28 strains ( Table 2 in online Technical Appendix). However, whether those serotypes cause more severe disease because of their hypervirulence or because they were also the most prevalently isolated strains in the community at that time was not clear (11,12). These possibilities are not mutually exclusive, but in fact may be related.…”
Section: Resurgence Of Severe Invasive Streptococcal Diseases and Emementioning
confidence: 99%